2014
DOI: 10.1039/c3lc51098k
|View full text |Cite
|
Sign up to set email alerts
|

A paper-based potentiometric cell for decentralized monitoring of Li levels in whole blood

Abstract: A novel approach to monitor Li levels in blood in decentralized (out of the lab) settings is presented. The approach uses a potentiometric cell fully made with filter paper as a support. Electrodes were built using carbon nanotubes ink to create a conductive path and a suitable polymeric membrane. Solid-state ion-selective electrodes for Li and a reference electrode were built and optimized. The results obtained on real samples of serum and whole blood are comparable with those obtained by conventional standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 39 publications
(45 reference statements)
1
78
0
Order By: Relevance
“…15,31 Several miniaturized potentiometric cells into which an all-solid-state ISE and reference electrode are integrated have been proposed. [14][15][16][17] The electrochemical performance of these all-solid-state reference systems is highly dependent on the solid contact between the reference membrane and the underlying electron conductor. We demonstrated previously that a highly capacitive interface between the ISE membrane and the solid contact provides for a high potential stability of all-solid-state ISEs, 27 and we have shown that the same is also true for reference electrodes with a reference membrane/solid contact interface.…”
Section: Introductionmentioning
confidence: 99%
“…15,31 Several miniaturized potentiometric cells into which an all-solid-state ISE and reference electrode are integrated have been proposed. [14][15][16][17] The electrochemical performance of these all-solid-state reference systems is highly dependent on the solid contact between the reference membrane and the underlying electron conductor. We demonstrated previously that a highly capacitive interface between the ISE membrane and the solid contact provides for a high potential stability of all-solid-state ISEs, 27 and we have shown that the same is also true for reference electrodes with a reference membrane/solid contact interface.…”
Section: Introductionmentioning
confidence: 99%
“…ISE's exhibit a high selectivity to lithium ions relative to the much higher concentration of sodium or potassium ions present in the sample, even though these have been reported to interfere with measurements [20]. In [18] a potentiometric cell was built using lithium ISE (by applying an ion selective polymer membrane) and a reference electrode, with a limit of detection to changes in Li + concentration of approximately 0.11mM. A possible issue with the use of ISE's is that the presence of large proteins in a physiological sample may deter the sensitivity of the electrodes towards Lithium, thus filtration of the sample may be required [16].…”
Section: B Alternative Lithium Sensing Methods 1) Electrochemical Mementioning
confidence: 99%
“…A possible issue with the use of ISE's is that the presence of large proteins in a physiological sample may deter the sensitivity of the electrodes towards Lithium, thus filtration of the sample may be required [16]. Response time for an ISE recording can be within 20-40 s [18].…”
Section: B Alternative Lithium Sensing Methods 1) Electrochemical Mementioning
confidence: 99%
See 1 more Smart Citation
“…Clinically established techniques in the measurement of blood lithium concentrations include flame emission photometry (FEP) and atomic absorption spectroscopy (AAS) [4,5] which require a laboratory setting and are not suitable for home use. Other non-clinically established techniques include potentiometry via ion sensitive electrodes (ISE's) with high affinity to Lithium [6], as well as capillary electrophoresis [7]. ISE methods as well as electrophoretic techniques require the use of specific ion selective membranes or the application of high voltage signals (in the order of kV) for ion separation respectively.…”
Section: Introductionmentioning
confidence: 99%